The Controlling Factors of the Natural Gas Hydrate Accumulation in the Songnan Low Uplift, Qiongdongnan Basin, China - Wei, Yang; Zenggui, Kuang; Jinfeng, Ren; Jinqiang, Liang; Hong, Lu; Zijie, Ning; Chenlu, Xu; Hongfei, Lai; Rui, Chen; Bin, Zhao; Jing, Chen; Xi, Zhang; et al. (Frontiers in Earth Science, 2022)
Hydrocarbon charging stages and natural gas hydrate accumulation models were established in the Songnan Low Uplift, Qiongdongnan Basin (QDNB), China. Detailed geochemical analysis, paleotemperature and paleopressure analyses, seismic interpretation, and hydrocarbon charging characterization were conducted to investigate the controlling factors of natural gas hydrate accumulation. The Yacheng and Lingshui formations in the Lingshui Sag were identified as effective source rocks. The δ13C1 values of the gas hydrates vary from −35.97‰ to −59.50‰, following a direction from the Sag Center to the Low Uplift, indicating that δ13C1 values became relatively lighter during gas migration. Seismic data evidence revealed that large-scale faults, laterally distributed sandstones, and gas chimneys were comprehensive, however efficient hydrocarbon migration pathways. Systematic overpressure was developed in the Yacheng and Huangliu formations, which offer sufficient hydrocarbon migration impetus. Hydrocarbon-bearing aqueous inclusions and their coexisting aqueous inclusions were observed in the Huangliu Formation in the Lingshui Sag, indicating four stages of hydrocarbon charging in the QDNB. Based on the comprehensive analysis in this research, two gas hydrate accumulation models were proposed in the Songnan Low Uplift, QDNB, as follows: 1) a mixture of gas migrated by large-scale faults and a thermogenic-biogenic mixed gas model and 2) gas hydrates from laterally distributed sandstones sealed by MTDs.